OP0235 A novel B cell specific IFN-I biomarker is associated with plasmablast numbers following B cell depletion therapy in SLE. (15th June 2017) - El-Sherbiny, YM; Yusof, MY Md; Hensor, E; Rawstron, A; Wittmann, M; Emery, P; Vital, EM
Abstract : Background: SLE is a Type I interferon (IFN-I) mediated disease with autoreactive B cells. Plasmablasts, the immediate progeny of B cells, are expanded in SLE and correlate with disease activity. We showed that their rate of regeneration after therapeutic B cell depletion with rituximab is variable and predicts relapse[1]. IFN-I has been shown in vitro to induce the differentiation of B cells into plasmablasts. We previously showed that therapeutic B cell depletion with anti-CD20 mAb leads to a transient reduction in CD20-negative plasmablasts, following which plasmablasts repopulate and their numbers predict clinical relapse. We developed tetherin as a flow cytometric, cell-specific marker for IFN-I response. Objectives: To test the hypothesis that memory B cell tetherin determines the rate of plasmablast repopulation after rituximab. Methods: 117 rituximab-treated SLE patients were studied prosectively using BILAG-2004 and flow cytometry. In 97 responders we tested plasmablasts at 6 months as a predictor of clinical relapse before 12 months to validate our previous finding. In 50 patients pre-rituximab and 28 patients post-rituximab we performed additional flow cytometry to measure tetherin on each cell subset. Expression of 18 ISGs was measured using Taqman on PBMCs and an ISG score calculated. Results: We divided clinical responders to rituximab into earlier relapse (12 months) or later relapse (>12 months). As in our published discovery cohort, plasmablasts were strongly predictive of clinical relapse. ROC analysis indicated that a plasmablast count of >0.0008 x 10 9 /L at 6 months yielded 73% (95% CI 45–92%) sensitivity and 90% (95% CI 56–99%) specificity in predicting earlier relapse; area under the curve of 0.86. Plasmablast numbers after rituximab were associated with Memory B cell tetherin (R=0.38, p=0.047) but not ISG score (R=0.24, p=0.219) (Table 1 ). In Pre-rituximab there was no relationship between any IFN assay and plasmablast count. After rituximab treatment there was no correlation between plasmablast count and ISG expression, nor with monocyte or NK cell surface tetherin. However, memory B cell tetherin MFI was positively correlated with plasmablast count (Table 1 ). Conclusions: Although interferon stimulated gene expression is commonly used to measure IFN-I activity, tetherin provides a cell-specific assay. We demonstrate that by measuring IFN-I response in B cells specifically, we could explain plasmablast differentiation, and thereby clinical outcome. Memory B cell tetherin is valuable to immunophetype SLE. References: Vital et al. Arthritis Rheum. 2011 Oct;63(10):3038–47. Disclosure of Interest: None declared